Development and optimization of tablea-cashew nut spread using response surface methodology - De Guzman, Vea Clarissa L.; Francisco, Ma. Leonora dL. (Quezon City College of Home Economics, University of the Philippines Diliman, 2017)
Response surface methodology was used to optimize formulations of tablea-cashew nut spread. Sixteen formulations with varying levels of cashew nut (25-90%), tablea syrup (5-70%) and sugar (5-55%) were processed using a three-component constrained simplex lattice design. Response variables, measured with consumers participating in the test, were color, aroma, spreadability, sweetness, flavor, and overall acceptability using a 9-point Hedonic scale. Using analysis of variance, results showed that all models were significant (p<0.05); thus, all predictive models were utilized to generate an overlay plot indicating the optimal region from where an optimal formulation for the spread can be obtained. Optimum formulations (consumer acceptance rating of > 6.0 for all attributes) for tablea-cashew nut spread were all combinations of 25-50% cashew, 45-70% tablea syrup, and 5-25% sugar, adding up to 100%. Verification of two formulations (within and outside the optimum) indicated no difference between predicted and observed values. Further studies on the individual raw materials can be done to better assess their interactions when used together in a food product. Physicochemical analysis of the spread can also be performed to correlate physicochemical characteristics with sensory responses. Also, preference testing can be done to test whether consumers want either tablea or cashew to dominate the overall flavor of the final product.
submitted June 2017
Thesis (B.S. Food Technology)--University of the Philippines Diliman.
Keywords: Chocolate processing -- Philippines